Faktor Determinan Kurangnya Pencapaian Target Imunisasi Dasar Lengkap di Puskesmas Elelim, Distrik Elelim, Kab. Yalimo Provinsi Papua Pegunungan - Susia Peyon; Maryati Sutarno (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Papua Mountains has the lowest achievement of complete basic immunization in Indonesia, only 8.9%. This reflects major challenges, such as limited infrastructure and accessibility. Immunization non-compliance increases the risk of the spread of preventable diseases, worsens the health burden, and threatens public health goals and overall well-being. To determine the influence of the role of health workers and maternal motivation on the achievement of complete basic immunization targets at Elelim Health Center, Elelim District, Yalimo Regency. Yalimo, Papua Mountains Province in 2025. This research design uses a quantitative analytical survey method with a cross-sectional approach. The number of samples is 83 people with a purposive sampling technique. Statistical data testing using the Chi-Square test. The results of the Chi-Square Test in the category of the role of health workers and maternal motivation obtained a p-Value of 0.000 (0.05), which indicates that there is a significant influence between the role of health workers and maternal motivation on achieving the target of complete basic immunization. There is an influence of the role of health workers and maternal motivation on achieving the target of complete basic immunization at the Elelim Health Center, Elelim District, Yalimo Regency, Papua Mountains Province. For health workers and cadres, it is hoped that health workers and cadres can be more active in providing education and support to mothers, as well as building motivation to achieve the target of complete basic immunization. Keywords: Achievement of Complete Basic Immunization Target, Mother's Motivation, Role of Health Workers.  ABSTRAK Papua Pegunungan memiliki pencapaian imunisasi dasar lengkap terendah di Indonesia, hanya 8,9%. Hal ini mencerminkan tantangan besar, seperti keterbatasan infrastruktur dan aksesibilitas. Ketidakpatuhan imunisasi meningkatkan risiko penyebaran penyakit yang dapat dicegah, memperburuk beban kesehatan, dan mengancam tujuan kesehatan masyarakat serta kesejahteraan secara keseluruhan. Mengetahui pengaruh peran petugas kesehatan dan motivasi ibu dengan capaian target imunisasi dasar lengkap di Puskesmas Elelim, Distrik Elelim, Kab. Yalimo Provinsi Papua Pegunungan tahun 2025. Desain penelitian ini menggunakan metode kuantitatif  survei analitik dengan pendekatan cross sectional. Jumlah sample sebanyak 83 orang dengan teknik pengambilan sampel purposive sampling. Uji statistik data menggunakan uji Chi-Square. Hasil Uji Chi-Square pada kategori peran petugas kesehatan dan motivasi ibu diperoleh nilai p-Value 0.000 ( 0.05), yang mengindikasikan bahwa adanya pengaruh yang signifikan antara peran petugas kesehatan dan motivasi ibu terhadap pencapaian target imunisasi dasar lengkap. Terdapat pengaruh peran petugas kesehatan dan motivasi ibu dengan capaian target imunisasi dasar lengkap di Puskesmas Elelim, Distrik Elelim, Kab. Yalimo Provinsi Papua Pegunungan. Untuk petugas kesehatan dan kader, diharapkan petugas kesehatan dan kader dapat lebih aktif dalam memberikan edukasi dan dukungan kepada ibu-ibu, serta membangun motivasi untuk mencapai target imunisasi dasar lengkap. Kata Kunci: Capaian Target Imunisasi Dasar Lengkap, Motivasi Ibu, Peran Petugas Kesehatan.